Perbandingan Faktor Risiko Gangguan Kesehatan Gigi dan Mulut Pada Usia 20-59 Tahun Berdasarkan Wilayah di Indonesia: Analisis Survei Kesehatan Indonesia (SKI) Tahun 2023 - Ayun, Khadijah Qurrata; Adisasmita, Asri, Prof (UI Scholars Hub, 2025)
Oral and dental health is one of the indicators of health, well- being, and quality of life. In addition, poor oral health can increase the economic burden, including treatment costs, loss of work productivity, and worsen the burden of other diseases. Globally, the average prevalence of dental and oral diseases is around 45%. In 2023, dental and oral health problems in Indonesia reach 57,6%. This study aims to analyze risk factors for dental and oral health disorders among people aged 20-59 years based on regions in Indonesia. This study uses a cross- sectional design. The secondary data used is data from the 2023 Indonesian Health Survey. The sample used was 479,886 respondents. The analysis was carried out by grouping by region Java-Bali and non Java-Bali. The dependent variable is dental and oral health disorders. The independent variables include age, gender, education level, place of residence, smoking status, consumption of sweet drinks, sweet foods, alcohol, frequency of tooth brushing, and visits to the dentist. Prevalence of dental and oral health disorders in Java-Bali (57,43%) and non Java-Bali (57,97%) is not significantly different. The highest risk factor in the Java-Bali and non Java- Bali regions is visits to the dentist in the past year. Therefore, there needs to be a national effort to encourage dental checkup as an important preventive care in the regions. Keywords: Dental and oral health, disorder, productive age, region